Future Ceiling Design Based on Fischer. Issue 3 (April 2021) - Li, Yuqi; Yang, Chenglong; Liao, Yusen; Li, Jiacheng
Abstract: This design cleverly integrates modern machinery and control technology into the home system, and cleverly combines intelligent machinery and intelligent life, making family life more intelligent, comfortable and convenient. Use the ceiling as the carrier to realize the three-dimensional home design, make full use of the indoor top space, and solve the problems of small residential space and difficult storage. The main functions contained in this device are stored indoors. The introduction of this design conforms to the trend of intelligent family life and greatly facilitates people's daily life.